A Malignant Neoplasm From the Jejunum With a MALAT1-GLI1 Fusion and 26-Year Survival History. (August 2020) - Prall, Owen William John; McEvoy, Christopher Robert Edward; Byrne, David John; Iravani, Amir; Browning, Judy; Choong, David Yew-Huong; Yellapu, Bhargavi; O'Haire, Sophie; Smith, Kortnye; Luen, Stephen James; Mitchell, Paul Leslie Ross; Desai, Jayesh; et al.
The transcription factor GLI1 is a critical effector of the sonic hedgehog pathway. Gene fusions that activate GLI1 have recently been reported in several tumor types including gastroblastoma, plexiform fibromyxoma, a subset of pericytomas, and other soft tissue tumors. These tumors arise in a wide variety of anatomical origins and have variable malignant potentials, morphologies, and immunohistochemistry profiles. In this case report, we describe a malignant tumor from the jejunum with a MALAT1-GLI1 gene fusion that expressed a truncated constitutively active GLI1 protein and GLI1 targets that were detectable by immunohistochemistry. The tumor showed high-grade epithelioid and spindle cell morphology, strongly expressed CD56, and focally expressed other neuroendocrine markers and cytokeratins, but not S100 protein or SMA. The tumor recurred multiple times in liver, soft tissue, and lung over the course of 26 years, the longest reported follow-up for a GLI1 fusion-associated tumor. These metastatic tumors were also composed of epithelioid and spindle cells, but showed lower morphological grade than the primary tumor. The metastatic tumors resembled the recently reported "malignant epithelioid neoplasms with GLI1 rearrangements." The tumor also had a relatively high tumor mutation burden for a sarcoma. This case report expands the sites of origin for GLI1 rearranged neoplasms and shows that despite being associated with high-grade morphology, these malignancies can be associated with very long-term survival.